First preclinical evaluation of [225Ac]Ac-DOTA-JR11 and comparison with [177Lu]Lu-DOTA-JR11, alpha versus beta radionuclide therapy of NETs - Maryana Handula; Savanne Beekman; Mark Konijnenberg; Debra Stuurman; Corrina de Ridder; Frank Bruchertseifer; Alfred Morgenstern; Antonia Denkova; Erik de Blois; Yann Seimbille (SpringerOpen, 2023)
Abstract Background The [177Lu]Lu-DOTA-TATE mediated peptide receptor radionuclide therapy (PRRT) of neuroendocrine tumors (NETs) is sometimes leading to treatment resistance and disease recurrence. An interesting alternative could be the somatostatin antagonist, [177Lu]Lu-DOTA-JR11, that demonstrated better biodistribution profile and higher tumor uptake than [177Lu]Lu-DOTA-TATE. Furthermore, treatment with alpha emitters showed improvement of the therapeutic index of PRRT due to the high LET offered by the alpha particles compared to beta emitters. Therefore, [225Ac]Ac-DOTA-JR11 can be a potential candidate to improve the treatment of NETs (Graphical abstract). DOTA-JR11 was radiolabeled with [225Ac]Ac(NO3)3 and [177Lu]LuCl3. Stability studies were performed in phosphate buffered saline (PBS) and mouse serum. In vitro competitive binding assay has been carried out in U2OS-SSTR2 + cells for natLa-DOTA-JR11, natLu-DOTA-JR11 and DOTA-JR11. Ex vivo biodistribution studies were performed in mice inoculated with H69 cells at 4, 24, 48 and 72 h after injection of [225Ac]Ac-DOTA-JR11. A blocking group was included to verify uptake specificity. Dosimetry of selected organs was determined for [225Ac]Ac-DOTA-JR11 and [177Lu]Lu-DOTA-JR11. Results [225Ac]Ac-DOTA-JR11 has been successfully prepared and obtained in high radiochemical yield (RCY; 95%) and radiochemical purity (RCP; 94%). [225Ac]Ac-DOTA-JR11 showed reasonably good stability in PBS (77% intact radiopeptide at 24 h after incubation) and in mouse serum (~ 81% intact radiopeptide 24 h after incubation). [177Lu]Lu-DOTA-JR11 demonstrated excellent stability in both media (> 93%) up to 24 h post incubation. Competitive binding assay revealed that complexation of DOTA-JR11 with natLa and natLu did not affect its binding affinity to SSTR2. Similar biodistribution profiles were observed for both radiopeptides, however, higher uptake was noticed in the kidneys, liver and bone for [225Ac]Ac-DOTA-JR11 than [177Lu]Lu-DOTA-JR11. Conclusion [225Ac]Ac-DOTA-JR11 showed a higher absorbed dose in the kidneys compared to [177Lu]Lu-DOTA-JR11, which may limit further studies with this radiopeptide. However, several strategies can be explored to reduce nephrotoxicity and offer opportunities for future clinical investigations with [225Ac]Ac-DOTA-JR11.